2015
DOI: 10.1155/2015/418724
|View full text |Cite
|
Sign up to set email alerts
|

Some Biochemical and Hematological Parameters among Petrol Station Attendants: A Comparative Study

Abstract: Objective. To describe selected biochemical and hematological parameters (blood picture, liver enzymes, and kidney functions) in petrol station attendants in Mansoura city. Methods. This is a comparative cross-sectional study. The exposed group included 102 petrol station attendants. They were compared to a matched group of healthy 102 male service and office workers at the Faculty of Medicine, Mansoura University. The results of blood picture, liver enzymes, and kidney functions were compared between both gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
27
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 23 publications
10
27
1
2
Order By: Relevance
“…In the present study, the significantly lower mean serum albumin among petrol station workers compared to the office clerks is in line with the published literature, where significantly decreased albumin levels in exposed people com-pared to the controls have been reported elsewhere (12-15). This finding is also in line with that observed among Egyptian petrol station attendants, where the mean levels of serum albumin and total protein were non-significantly lower than those of their counterparts (16). Experimentally, lead acetate was found to have a significant reduction in total soluble proteins and albumin but not on plasma globulins (17).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, the significantly lower mean serum albumin among petrol station workers compared to the office clerks is in line with the published literature, where significantly decreased albumin levels in exposed people com-pared to the controls have been reported elsewhere (12-15). This finding is also in line with that observed among Egyptian petrol station attendants, where the mean levels of serum albumin and total protein were non-significantly lower than those of their counterparts (16). Experimentally, lead acetate was found to have a significant reduction in total soluble proteins and albumin but not on plasma globulins (17).…”
Section: Discussionsupporting
confidence: 88%
“…However, a significant increase in the activities of ALT and AST was found among such attendants with long-term exposure (6-10 years) to petrol vapors in comparison to the controls. In line with this finding, non-significant AST differences were found among Egyptian petrol station attendants compared to their corresponding controls (16). In contrast, higher serum transaminase activities were observed among fuel-filling workers of Sulaimani city compared to the controls, though these values were within the normal range for clinical diagnosis of hepatic injury (27).…”
Section: Discussionmentioning
confidence: 56%
“…This finding is consistent with other which may be due to degradation of purines and pyrimidines or to an increase of uric acid level by either over production or inability of excretion (Abdel Aziz, et al, 2006). Whereas, serum creatinine (0.698±0.025 mg/dl) was within the normal ranges and had no significant differences with those of controls (0.657±0.024 mg/dl), this results are accepted with previous study (Abou-ElWafa, et al, 2015). Most of chemical substances are toxic to many organ systems including the kidney (W. Qin, et al, 2012), which may be attributed to an increase in liberating toxic metabolites including reactive oxygen species.…”
Section: Resultssupporting
confidence: 80%
“…It is worth noting that significant decreases in WBC, RBC, and platelet counts, and even the presence of isolated thrombocytopenia, have already been observed in human populations exposed to high levels of benzene in classic hematological exams (Abou-El Wafa et al, 2015;Smith, 2010). Abou-ElWafa et al,(2015) reported a mean RBC count, hemoglobin level, and HCT significantly lower in gas station workers compared to the control group. In our study we found a range of cell alterations in classic hematological exams (female CHGM, typical lymphocytes, monocytes, male hematocrit), evidencing a non-specific cell effect and the clear involvement of the myeloid and lymphoid cell sets by BTEX exposure.…”
Section: Discussionmentioning
confidence: 94%